Evaluating the Impact of Bilateral Contracts on the Offering Strategy of a Price Maker Wind Power Producer - Rashidizadeh-Kermani, Homa; Vahedipour-Dahraie, Mostafa; Shafie-khah, Miadreza; Siano, Pierluigi (IEEE, 2022)
Due to the high penetration of wind power generation in power systems and electricity markets, wind power plants (WPPs) can, in some scenarios, influence the market prices and exercise market power in the day-ahead (DA) market. In order to evaluate the capability of WPPs to directly act as price-maker, this article proposes the strategic offering of a WPP in the DA market by using a bilevel stochastic optimization approach. The primary objective of the proposed model is to maximize the WPP's expected profit by strategically offering in DA market while minimizing the energy deviations in the regulating market. Moreover, the WPP can also sign bilateral contracts with customers to supply their required energy. In the subproblem, the system operator tends to minimize the sum of the total generation costs minus the sum of the total demand benefits. The effect of bilateral contracts on the strategic offering of WPP in the DA market and its impact on the transmission margin are also investigated. Results on real cases show that when the WPP enters into a bilateral contract, it should consider the effect of such contracts on the offering strategy to the DA market. The effects of bilateral contracts on the regulating market are also examined.
Keywords: Bilateral contract; contracts; Costs; Informatics; line congestion; load modeling; Market power; stochastic processes; strategic offering; Wind power generation; wind power plant (WPP); renewable energy sources; fi=Sähkötekniikka|en=Electrical Engineering|